Quality of Root Canals Performed by the Inaugural Class of Dental Students at Libyan International Medical University - Ranya F. Elemam; Ziad Salim Abdul Majid; Matt Groesbeck; Álvaro F. Azevedo (Hindawi Limited, 2015)
Objective. The purpose of this study was to radiographically evaluate technical quality of root canal fillings performed by dental undergraduates at Libyan International Medical University in Libya. Methods. Root canal cases were treated at university dental clinic from the fall of 2012 to the fall of 2013 by the fourth and fifth year dental students. Students used step-back preparation and cold lateral compaction in the treatment. Radiographs were reviewed over a two-year period from initial procedure to final restoration. Radiographs were evaluated for adequacy or inadequacy by length, density, and taper. Length inadequacy was classified as short or overextended. Overall quality was considered "adequate" based on all three variables. Chi-square tested differences between teeth groupings and adequacy classification. Significant p value results were adjusted by Bonferroni correction. Results. Adequate length of root canal fillings were observed in roughly half of all samples (48.6%). Density was adequate in 75.8% of the samples. Taper was observed as adequate in 68.8%. Higher quality was evident in anterior teeth (plus premolars) versus molars (65.6% versus 43.3%, resp.; p<0.04). Conclusion. Overall quality of endodontic treatment performed by undergraduate dental students was adequate in 53.9% of the cases. Significant opportunity exists to improve the quality of root canals provided by dental students.